Identification and Characterization of Two Novel Compounds: Heterozygous Variants of Lipoprotein Lipase in Two Pedigrees With Type I Hyperlipoproteinemia - Wang, Shuping; Cheng, Yiping; Shi, Yingzhou; Zhao, Wanyi; Gao, Ling; Fang, Li; Jin, Xiaolong; Han, Xiaoyan; Sun, Qiuying; Li, Guimei; Zhao, Jiajun; Xu, Chao (Frontiers in Endocrinology, 2022)
Background Type I hyperlipoproteinemia, characterized by severe hypertriglyceridemia, is caused mainly by loss-of-function mutation of the lipoprotein lipase (LPL) gene. To date, more than 200 mutations in the LPL gene have been reported, while only a limited number of mutations have been evaluated for pathogenesis. Objective This study aims to explore the molecular mechanisms underlying lipoprotein lipase deficiency in two pedigrees with type 1 hyperlipoproteinemia. Methods We conducted a systematic clinical and genetic analysis of two pedigrees with type 1 hyperlipoproteinemia. Postheparin plasma of all the members was used for the LPL activity analysis. In vitro studies were performed in HEK-293T cells that were transiently transfected with wild-type or variant LPL plasmids. Furthermore, the production and activity of LPL were analyzed in cell lysates or culture medium. Results Proband 1 developed acute pancreatitis in youth, and her serum triglycerides (TGs) continued to be at an ultrahigh level, despite the application of various lipid-lowering drugs. Proband 2 was diagnosed with type 1 hyperlipoproteinemia at 9 months of age, and his serum TG levels were mildly elevated with treatment. Two novel compound heterozygous variants of LPL (c.3G>C, p. M1? and c.835_836delCT, p. L279Vfs*3, c.188C>T, p. Ser63Phe and c.662T>C, p. Ile221Thr) were identified in the two probands. The postheparin LPL activity of probands 1 and 2 showed decreases of 72.22 ± 9.46% (p<0.01) and 54.60 ± 9.03% (p<0.01), respectively, compared with the control. In vitro studies showed a substantial reduction in the expression or enzyme activity of LPL in the LPL variants. Conclusions Two novel compound heterozygous variants of LPL induced defects in the expression and function of LPL and caused type I hyperlipoproteinemia. The functional characterization of these variants was in keeping with the postulated LPL mutant activity.